2012
DOI: 10.1210/en.2011-1864
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Receptor Agonists and the Thyroid: C-Cell Effects in Mice Are Mediated via the GLP-1 Receptor and not Associated with RET Activation

Abstract: Liraglutide and exenatide are glucagon-like peptide receptor (GLP-1R) agonists used in the treatment of type 2 diabetes. Both molecules have been associated with the development of thyroid C-cell tumors after lifetime exposure in rodents. Previously, it has been reported that these tumors are preceded by increased plasma calcitonin and C-cell hyperplasia. We can now document that the murine C-cell effects are mediated via GLP-1R. Thus, 13 wk of continuous exposure to GLP-1R agonists was associated with marked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 22 publications
2
75
1
1
Order By: Relevance
“…Our data indicate that Ex-4 stimulates calcitonin secretion and thus can induce an inhibition of resorption. However we found no effect of LIR on calcitonin secretion while studies have reported that both Ex-4 and LIR stimulate calcitonin secretion (63,64). Our data are not completely consistent with this mechanism since we observed an increase in resorption surfaces with GLP-1 agonists whereas other studies have reported that calcitonin decreased resorption surfaces (65).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our data indicate that Ex-4 stimulates calcitonin secretion and thus can induce an inhibition of resorption. However we found no effect of LIR on calcitonin secretion while studies have reported that both Ex-4 and LIR stimulate calcitonin secretion (63,64). Our data are not completely consistent with this mechanism since we observed an increase in resorption surfaces with GLP-1 agonists whereas other studies have reported that calcitonin decreased resorption surfaces (65).…”
Section: Discussioncontrasting
confidence: 99%
“…Another reason could be that GLP-1 agonists do not act directly on bone cells. It has been shown that GLP1-R is also expressed in C cells of the thyroid gland and exerts, when activated by GLP-1 or its stable analogues, a stimulating effect on calcitonin secretion in rodents (63,64), a potent inhibitor of bone resorption. As proposed by Yamada et al (29), GLP-1 agonist effects on bone might be indirect rather than direct, acting mainly by targeting calcitonin secretion from the thyroid to modulate bone turnover.…”
Section: Discussionmentioning
confidence: 99%
“…Calcitonin is one of the most efficient inhibitors of bone resorption in vitro (Zaidi et al 1990, Moonga et al 1992. Evidence from previous studies suggests that basally, male Glp1r KO mice present with a 2.5-fold increase in circulating plasma calcitonin (Madsen et al 2012). As regard to the inhibitory action of calcitonin on bone resorption, it would be legitimate to hypothesize that bone resorption should be the primary target of calcitonin increase.…”
Section: Discussionmentioning
confidence: 99%
“…Liraglutide and exenatide have been associated with the development of thyroid C-cell tumors in rodents after life-time exposure at supratherapeutic doses [169]. Furthermore, a 13-week continuous exposure to GLP-1 receptor agonists induced marked increases in plasma calcitonin and in the incidence of C-cell hyperplasia in wild-type mice, but not in GLP-1 receptor knockout mice [170]. In contrast to the results in rodents, in vivo animal studies with cynomologus monkeys did not show any liraglutideinduced calcitonin release or any effect on relative C-cell fraction in the thyroid gland after 87 weeks at doses up to 60-fold higher than the highest dose recommended in humans [169].…”
Section: Cancermentioning
confidence: 99%